Spatial deixis and demonstratives in the Kirati languages - Rai, Tara Mani (Gipan, 2024)
This paper delves into the spatial deixis (deictic) embedded in the Kirati languages namely Bantawa, Bayung, Chamling, Dumi, Dungmali, Koyee, Khaling, Kulung, Limbu, Lohorung, Nachhiring, Puma, Sampang, Thulung, Wambule and Yamphu within the comparative and cross-linguistic context. The data drawn in this paper were collected from the direct elicitation from the speakers of more than a dozen Kirati languages. The findings of this study reveal that the Kirati languages share the spatial deictic features almost in the same pattern. The Kirati languages exhibit the locative suffixes for 'above, up', 'below, down' and 'across' indicating by various deictic suffixes. Vertical deictic like 'up here', 'down here' and 'over here' are realized in different ways in terms of the deictic suffixes. It is interesting that all the Kirati languages are not treated in the same way in both of the vertical deixis, i.e. Bantawa, Dungmali and Wambule have the same lexicon to denote 'above' and 'over'. But the other languages discussed in this article are treated in both of the paradigms. The deictic roots are also nominalized with suffixes in the Kirati languages. Typologically, Dungmali, Bantawa, Thulung, and Puma might be grouped into one whereas the languages like Yamphu, Koyee, Khaling, Dumi and Lohorung may be grouped into another category. There are some other Tibeto-Burman languages like Gurung, Tamang and Manangba that may be grouped into third category the way they are treated with the locational suffixes. The rest of the languages share the individual locational markers.